Determination of Frequency of Near Miss Morbidity in Obstetrical patients Presenting in Emergency at Arif Memorial Hospital - Uzma Aziz,, Asima Munawar, Madiha Afzal, Asma Yasin, Asifa Noreen, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The definition of near miss event is: acute obstetric complication that endangers the survival of an obstetric patient immediately but not resulting in her death by chance or because of the hospital based obstetric care she receives during antenatal, intrapartum or postpartum period either after delivery or termination of pregnancy. Aim: To find frequency of near miss morbidity in pregnant females presenting at emergency department in critical condition at Arif Memorial Teaching Hospital was the objective of our study. Methods: This was a descriptive case series that was conducted at department of Obstetrics and Gynecology Arif Memorial Teaching Hospital/Rashid Latif Medical College Lahore for one year from March 2021 till February 2022 after approval from Ethical Review board of RLMC. A total of 310 females meeting inclusion criteria were included in this study. After taking informed consent, their age, obstetric history, gestational age (on USG), parity, and demographic details was obtained. All patients were followed till delivery. Near-miss was identified as per operational definition and cause was recorded. All patients were managed efficiently as per standard protocol. Data was analyzed by using SPSS version 20. Results: Most of the cases were with mean age of 31.43 ± 7.25 years with age range of 16 as minimum and 45 as maximum age. The mean gestational age at presentation was 36.63 ± 2.82 weeks with minimum and maximum gestational age as 32 and 41 weeks. According to operational definition near miss morbidity was diagnosed in 30 (9.65%) in which severe anemia was seen in 11 (36.67%) preceding by 6 (20%) as severe hemorrhage, hypertensive disorder each, 5 (16.67%) females had sepsis and 2 (6.67%) had uterine rupture. Conclusion: The frequency of near miss morbidity in pregnant females presenting at emergency department in critical condition at Arif Memorial Hospital was relatively high and common cause was severe anemia.